Second Street project sign ready for debut (Raton, NM Raton Range, 1996)
Article on the unveiling of a second street sign.
Master List item # 2
File location is in the Raton File Cabinet
Keywords: Mileta, Pete Jr; Ciammaichella, Debbie; Sisneros, Patti; McQueary, Kathy; New Mexico State Highway Department; Welcome Center; Local History; New street sign; City Projects; Oxen; Schooner; Raton, New Mexico; Albuquerque, New Mexico